Subcapsular liver hematoma after extracorporeal shock wave lithotripsy, a rare complication - Molina, Gabriel A (J Surg Case Rep, 2019)
Extracorporeal shock wave lithotripsy (ESLW) is a common and relatively safe procedure, with a high success rate and low adverse effects. Complications of this procedure are usually limited to the kidneys and almost always resolve spontaneously. However, on rare occasions, a frightening complication, as a hematoma of a parenchymatous organ, such as the liver can appear. Abdominal pain is usually the only manifestation when a liver hematoma develops, and should always be investigated, as this dreaded complication can put the patient’s life at risk. Conservative treatment is usually the treatment of choice, nevertheless, on severe cases that do not respond to conservative measures, surgery or embolization is necessary. We report the case of a 38-year-old male who underwent ESWL, 12 h after the procedure he presented to the emergency room with severe abdominal pain, after complementary exams a liver hematoma was detected. Following conservative management, the patient fully recovered.